Challenges in healthcare access for young people living with HIV: A review - Sarmad Muhammad Soomar; Warisha Qamar; Zahida Azizullah; Tazeen Saeed Ali (International Society of Global Health, 2023)
# Background Young People Living with HIV (YPLH) face numerous obstacles when trying to get medical care. In some parts of the world, AIDS-related mortality, and infection rates among people in this age continue to rise. The main causes of this include infrastructural challenges, concerns about unintentional disclosure and confidentiality, and the still-limited attitudes of healthcare professionals towards these age groups. This review article highlights the key aspects of access-related problems based on a thorough literature search and a synthesis of the available data about the difficulties the YPLH experiences. # Methods We looked through the last 15 years' worth of English-language studies that were conducted worldwide and published in the databases MEDLINE, PUBMED, MEDILINE, GOOGLE SCHOLAR, COCHRANE, and SCIENCE DIRECT. 35 articles fully meeting the inclusion criteria were included. # Results The literature review identified four overarching themes in terms of accessibility, including financial and insurance-related issues, workforce challenges, lack of knowledge and approachability issues associated with infrastructure and long travel distances. Furthermore, acceptability issues related to stigma, disclosure, discrimination, and low social support. The information was categorized from literature synthesis and was listed under the specific category that were decided earlier while beginning the search. These subcategories defined challenges to young people's access to HIV healthcare regarding affordability, acceptability, availability and approachability. # Conclusions YPLH encounters a multitude of challenges. These difficulties may be caused by structural reasons like social pressure, personal & societal ignorance about HIV, restricted access to HIV prophylaxis, and regulatory impediments. The findings imply that to facilitate the readily accessible HIV care services for youth it is vital to increase society's and healthcare professionals' awareness of HIV at every level.